Analisis Semiotika Pesan Dakwah Bunda Aniqq Alfaqiroh dalam Streaming YouTube “TERAPI MEMAAFKAN” - Romadlany, Zakiyah; Nazilah, Solihatun (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Abstract: In today's digital era, technology has made it easier for people to share and access various types of information, including the dissemination of Islamic teachings or dakwah. YouTube has become one of the platforms that provide opportunities for preachers to convey Islamic teachings in a more creative and engaging way for audiences. One prominent figure in digital dakwah is Bunda Aniqq Alfaqiroh, who, through YouTube streaming on PPA Institute, delivers content with themes of spiritual motivation. This study aims to analyze dakwah messages in the YouTube streaming titled